Performance investigation of a high-field active magnetic regenerator. (15th February 2019) - Teyber, Reed; Holladay, Jamelyn; Meinhardt, Kerry; Polikarpov, Evgueni; Thomsen, Edwin; Cui, Jun; Rowe, Andrew; Barclay, John
Highlights: A 100 K temperature span is measured with a bespoke magnetic refrigerator. Simulations assert the importance of fluid density and field strength on efficiency. An optimization of the material composition yields an efficient gas liquefier. Abstract: Regenerative magnetic cycles are of interest for small-scale, high-efficiency cryogen liquefiers; however, commercially relevant performance has yet to be demonstrated. To develop improved engineering prototypes, an efficient modeling tool is required to screen the multi-parameter design space. In this work, we describe an active magnetic regenerative refrigerator prototype using a high-field superconducting magnet that produces a 100 K temperature span. Using the experimental data, a semi-analytic AMR element model is validated and enhanced system performance is simulated using liquid propane as a heat transfer fluid. In addition, the regenerator composition and fluid flow are simultaneously optimized using a differential evolution algorithm. Simulation results indicate that a natural gas liquefier with a 160 K temperature span and a second-law efficiency exceeding 20% is achievable.